2015
DOI: 10.1007/s10439-015-1442-0
|View full text |Cite|
|
Sign up to set email alerts
|

AAMP Regulates Endothelial Cell Migration and Angiogenesis Through RhoA/Rho Kinase Signaling

Abstract: Angiogenesis is a complicated process including endothelial cell proliferation, migration and tube formation. AAMP plays a role in regulating cell migration of multiple cell types. The purpose of this study was to investigate whether AAMP regulates angiogenesis, and to clarify the role of AAMP in the VEGF-induced angiogenesis. We found that AAMP expressed in multiple cell types and mainly localized in cytoplasm and membrane in vascular endothelial cells. Using tube formation assay in vitro and aortic ring assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…We paid special attention to biomechanical regulation of cell migration in which actomyosin tension plays a critical role. Our previous studies have confirmed a leading role of actomyosin tension in regulating cell migration and angiogenesis, an essential step in generating atherosclerosis plaques (Qiu et al, ; Hu et al, ).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…We paid special attention to biomechanical regulation of cell migration in which actomyosin tension plays a critical role. Our previous studies have confirmed a leading role of actomyosin tension in regulating cell migration and angiogenesis, an essential step in generating atherosclerosis plaques (Qiu et al, ; Hu et al, ).…”
Section: Introductionsupporting
confidence: 68%
“…In 2D migration, actomyosin tension generates traction forces to translocate cell body and regulate assembly of focal adhesions through adhesions (Ridley et al, ). Our previous studies have implicated the important roles of cytoskeletal reorganization and focal adhesion assembly in cell adhesion and migration when the cells were overexpressing Id1 (Qiu et al, ), treated with oxLDLs (oxidized low‐density lipoprotein) in static conditions (Qiu et al, ; Qiu et al, ), or shear flow (Wei et al, ; Xie et al, ), placed on various matrices (Shen et al, ; Shen et al, ; Teng et al, ; Shen et al, ; Hu et al, ). We paid special attention to biomechanical regulation of cell migration in which actomyosin tension plays a critical role.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these pro-angiogenic and environmental factors, endothelial cells initiate angiogenic processes [3,4], which can be categorized as vascular sprouting [5], cell proliferation [6], cell migration [7], tube formation [8], and vascular stabilization [9]. Notably, during these angiogenic processes, endothelial cells dynamically alter cell mechanics, and physiological components determined by cytoskeletal rearrangement [10], focal adhesion formation [11], and contractile force [12], have also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the response to these pro-angiogenic factors and environments, vascular endothelial cells (ECs) initiate angiogenic process including vascular sprouting, cell proliferation, cell migration, tube formation, and vascular stabilization [3,4]. Notably, during these angiogenic process, ECs dynamically changes of cell mechanics that are mechanical and physiological characters determined by cytoskeletal rearrangement [5], focal adhesion formation [6], and contractile force [7], have been also observed.…”
Section: Introductionmentioning
confidence: 99%